EFL STUDENTS’ PERCEPTION OF TURNITIN FOR DETECTING PLAGIARISM ON ACADEMIC WRITING - Nova, Muhamad; Utami, Westi Haryanti (UPI Press, 2018)
As one of the negative impacts of technology development, the easy access to any information on the internet creates a new problem on academic integrity, in which the students take other’s works and claim as theirs. This phenomenon is termed as plagiarism which is against the academic ethics and honesty. Many universities have fought back the plagiarism cases and used plagiarism detection software as their tools in detecting plagiarism. Turnitin, as one of plagiarism detection software widely used in many universities, has been claimed as effective software in detecting plagiarism. However, prior studies have also revealed its inaccuracy in dealing with plagiarism cases. Reflecting from the both views of Turnitin, students’ view on its utilization may bring an essential consideration on the existence of Turnitin in detecting plagiarism. Therefore, this study aimed to investigate the utilization of Turnitin based on students’ perspective and explored their responses and perceptions toward plagiarism detected by Turnitin. A case study was conducted in one classroom consisted of 20 EFL students in a university in Bandung, Indonesia. The data were taken from self-reflection questionnaire and the result shows that many students had unexpected results due to their misunderstanding about plagiarism and Turnitin system. It led to students’ unsatisfying responses toward their result of similarity percentage from Turnitin. Even though several benefits on writing skill improvement were found by the students, the inaccuracy result of Turnitin evaluation raised their negative attitude toward its utilization as well. Therefore, equal understanding between the lecturer and the students on plagiarism and Turnitin system is needed. Moreover, lecturer’s cross-checking, feedback on students’ academic writing, and additional change on the system configuration in detecting plagiarism are required to avoid any misconception of plagiarism. Further research on different respondents or different plagiarism detection software is recommended to be conducted.